Revision of Toxoceratoides royeri (d'Orbigny, 1842) and its bearing on the systematics of the Aptian Acrioceratidae Vermeulen, 2004 (Ammonoidea, Ancyloceratina, Ancyloceratoidea). (August 2018) - Bulot, Luc G.; Frau, Camille; Pictet, Antoine
Abstract: The acrioceratid ammonite genus Toxoceratoides Spath has long been used to accommodate any late Barremian or Aptian species that show morphological similarities with its type species Toxoceratoides royeri (d'Orbigny). The revision of T. royeri and its allied species T. rochi Casey has convinced us that new genera should be introduced for some Aptian forms that were previously referred to Toxoceratoides . These are Klingerites gen. nov. (type species: Toxoceratoides ? haughtoni Klinger & Kennedy), Richardreymentella gen. nov. (type species: Ancyloceras patagonicum Stolley), Immelites gen. nov. (type species: Tonohamites multituberculatus Immel & Guoxiong), Jenslehmannella gen. nov. (type species Jenslehmannella bangestanense gen. et sp. nov.). This contribution also reconsiders the taxonomic value of Tonohamites Spath, Colomboceratoides Etayo Serna and Raymondcaseyites Avram. The new taxonomic treatment proposed herein outlines the diversity and provincialism of the Acrioceratidae during Aptian times and questions the alleged cosmopolitan distribution of Toxoceratoides .